NFE2L3 Inhibition Induces Cell Cycle Arrest at the G0/G1 Phase in Colorectal Cancer Cells through Downregulating CCND1 and pRb1-ser807/811. (5th May 2019) - Zhang, Lihua; Hu, Dong-Li; Tang, Baiyou; Cheng, Yu; Jiao, Chuan; Cheng, Lin; Tan, Zhi-Rong; Zhou, Hong-Hao
Abstract : The molecular mechanism for colorectal cancer to develop remains unelucidated. To find biomarkers related to colorectal cancer development, we analyzed the gene expression profile of 380 colorectal cancer patients and 51 healthy controls by R software. Finally, 1579 upregulated differential expression genes (DEGs) and 3218 downregulated DEGs were identified. Then, the top 20 upregulated DEGs were compared with 181 upregulated DEGs that we reported previously, and 11 overlapped DEGs were found. NFE2L3 (nuclear factor, erythroid 2-like 3) was among those overlapped DEGs and was rarely reported in colorectal cancer. Real-time polymerase chain reaction (PCR) results showed that higher NFE2L3 expression levels were identified in paired tumor samples than in paratumor samples (48 paired samples). Flow cytometry analysis revealed that the cell cycle was arrested at the G0/G1 phase after inhibition of NFE2L3 in both HCT116 and SW480 cell lines. Western blot detection showed that CCND1 and phosphorylated Rb transcriptional corepressor 1 at ser-807/811 (pRb1-ser807/811) expression levels were downregulated when NFE2L3 was inhibited in those two cell lines. A significant positive correlation was observed between NFE2L3 and CCND1 expression levels in colorectal tissue samples. These evidences indicate that downregulation of NFE2L3 induces cell cycle arrest at the G0/G1 phase through downregulation of CCND1 and pRb1-ser807/811.